Anglicisms in Spanish gastronomy: New words for new eating habits - Carmen Luján-García (Sintagma, 2023)
The growing tendency to develop a self-awareness about the need to consume healthier food and have healthier habits of life has increased the presence of anglicisms that designate new concepts. It is well known that English has gained a prominent position, due to its role of international means of communication and due to the positive values such as prestige and modernity associated with this language. This study explores the growing use of English lexical items by Spanish online press. It also examines the inclusion of a sample of food-related terms in Spanish reputable lexicography sources. Finally, the degree of knowledge and use of these English lexical items is examined by administering a survey to a sample of 130 Spanish university students. Findings suggest that English borrowings are quite extended among youngsters, but many of these anglicisms are more known than used by participants. To conclude, English is inevitably gaining ground to other foreign languages, traditionally associated with food and gastronomy, such as French.